A novel synthesis of an Fe3+/Fe2+ layered double hydroxide ('green rust') via controlled electron transfer with a conducting polymer. Issue 24 (17th May 2017) - Kim, Min-Sung; Kim, Tae-Hyun; Seo, Young Sun; Oh, Jae-Min; Park, Jin Kuen
Abstract : We demonstrate one simple way to produce crystalline green rust by controlling the electron transfer properties of a conducting polymer with a polyanionic macromolecule and the formation mechanism has been studied. Abstract : This report examines the influence of a conducting polymer on the crystal growth of labile green rust (GR) through hybridization with polypyrrole. All hybrids used in this study were prepared via one-pot co-precipitation at neutral pH, with specific stoichiometric ratios among all chemical species. The role of the conducting polymer and the effective stoichiometric ratio were demonstrated to facilitate the crystal growth of GR.